2012
DOI: 10.3892/mmr.2012.1067
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of pancreatic-duodenal homeobox 1 expression in breast cancer patients: A mechanism of proliferation and apoptosis in cancer

Abstract: Abstract. Pancreatic-duodenal homeobox 1 (PDX-1) is a transcription factor that regulates embryological pancreas development and insulin expression in adult islets. The current study investigated the expression profile and potential role of PDX-1 in breast cancer. Immunohistochemistry was performed to determine the expression pattern of PDX-1 in breast cancer and adjacent benign breast tissues. In addition, cell proliferation and the cell cycle were evaluated following the transient inhibition of PDX-1 with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“…In the third step, we assessed the expression levels of the proliferation marker Ki-67 in our study cohort and observed significant upregulation in HNC tumor tissues compared with adjacent control tissues. A similar pattern of Ki-67 overexpression has been reported in different cancers (33, 34). Jiang et al (35) reported that Ki-67 overexpression is related to increased tumor proliferation, recurrence and metastasis.…”
Section: Discussionsupporting
confidence: 85%
“…In the third step, we assessed the expression levels of the proliferation marker Ki-67 in our study cohort and observed significant upregulation in HNC tumor tissues compared with adjacent control tissues. A similar pattern of Ki-67 overexpression has been reported in different cancers (33, 34). Jiang et al (35) reported that Ki-67 overexpression is related to increased tumor proliferation, recurrence and metastasis.…”
Section: Discussionsupporting
confidence: 85%